2008
DOI: 10.1177/1356389007084673
|View full text |Cite
|
Sign up to set email alerts
|

Realistic Evaluation of an Illicit Drug Deterrence Programme

Abstract: This article describes an evaluation conducted in a region of northern Italy, based on the realistic evaluation approach.This case study is related to the application at regional level of national legislative measures against personal drug consumption, the so-called Article 75, through the implementation of a pilot programme. Article 75 DPR 309/90, is a `sanctions-based' intervention mainly based on the mechanism `threat—dissuasion', such that people who are found in possession of illicit drugs for personal us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 4 publications
1
18
0
1
Order By: Relevance
“…It promotes the notion that prevention planning and evaluation are intertwined, so that intervention and evaluation research should not be separated. This is in line with the modern and real-life concepts of theorybased evaluation (Birckmayer & Weiss, 2000;Leone, 2008): 'what works with whom in which context?' For this purpose, evaluation must be closely interlinked with project planning, working hypotheses and implementation, instead of being a separate or external research study.…”
supporting
confidence: 79%
“…It promotes the notion that prevention planning and evaluation are intertwined, so that intervention and evaluation research should not be separated. This is in line with the modern and real-life concepts of theorybased evaluation (Birckmayer & Weiss, 2000;Leone, 2008): 'what works with whom in which context?' For this purpose, evaluation must be closely interlinked with project planning, working hypotheses and implementation, instead of being a separate or external research study.…”
supporting
confidence: 79%
“…[285][286][287] Alongside realist approaches that have been applied to consider 'whole interventions', more selective analyses of the discrete components of an intervention are depicted in studies such as Leone's evaluation of an illicit drug deterrence programme. 288 This sanctions-based intervention is considered only with regard to the effects of its mandatory interview component. Similar approaches are demonstrated in other realist 290 Thus, it may be argued that previous applications of realist inquiry in health care have applied the concept of intervention inconsistently.…”
Section: Interventionmentioning
confidence: 99%
“…Realistic evaluation developed with the aim of attempting to overcome the difficulties associated with measurement and the effects of causation within complex social systems (Wilson and McCormack 2006). According to realistic evaluation, the causal power of a programme lies in the underlying mechanisms and in the basis theory of how programme resources will influence outcomes in a particular context (Leone 2008). Context is the background circumstance that encourages or enables a particular group of stakeholders to be assembled for negotiation.…”
Section: Critical Realism: a Brief Overviewmentioning
confidence: 99%
“…These authors argued that realistic evaluation can foster reflexive inquiry that involved transforming culture and changing roles. Leone (2008) stated that a realistic evaluation approach identified that accessibility to the service, professional qualifications of the operators, their different strategies and treatment flexibility is what helped to explain the successful implementation of an illicit drug deterrence programme. The availability of a more flexible and tailored intervention was the main attribute that improved participation in the programme.…”
Section: Realistic Evaluation In Health-care and Health Promotionmentioning
confidence: 99%